Testing the Weak Form Market Efficiency: Evidence from the Casablanca Stock Exchange - Guendouz, Imane (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
In the three classifications of market efficiency, the weak form efficiency is the one that states past stock price movements cannot be used to forecast future prices and they follow a random walk. This study tests the weak form efficiency for the Casablanca Stock Exchange using parametric and non-parametric tests and studies the behavior of stock prices. Specifically, four parametric and non-parametric tests, namely the serial correlation test, the runs test, the unit root tests (i.e., the Augmented Dickey-Fuller (ADF) and Phillips Perron (PP) test), and the variance ratio test are used to test for the weak form market efficiency. The findings of all four empirical tests find that the Casablanca Stock Market is not weak form efficient and stocks prices follow a random walk. This finding implies that the technical analysis used for predicting the future stock prices is useless. Keywords: the weak from efficiency, the random walk, the Casablanca Stock

ÖZ: Piyasa etkinliğinin üç sınıflandırmasının biri olan zayıf biçim etkinlik, geçmiş hisse senedi fiyat hareketlerinin gelecekteki fiyatları tahmin etmek için kullanılamayacağını ve hisse senedi fiyatlarının rastgele bir yürüyüşü izlediklerini öne sürmektedir. Bu çalışma, Kazablanka Borsası’nın zayıf biçim etkinliğini parametrik ve parametrik olmayan testler kullanarak test etmekte ve hisse senedi fiyatlarının davranışını incelemektedir. Spesifik olarak, dört parametrik ve parametrik olmayan testler, yani seri korelasyon testi, tekrarlar testi, birim kök testleri (Genişletilmiş Dickey-Fuller (ADF) testi ve Phillips Perron (PP) testi) ve varyans oranı testi, zayıf biçim piyasa verimliliğini test etmek için kullanılmıştır. Bu dört testin sonuçları Kazablanka Borsası'nın zayıf etkin olmadığını ve hisse senedi fiyatlarının rastgele bir seyir izlediğini göstermektedir. Sonuçlar gelecekteki hisse senedi fiyatlarını tahmin etmek için kullanılan teknik analizin kullanılmasını önermemektedir. Anahtar Kelimeler: zayıf biçim etkinlik, rastgele yürüyüş, Kazablanka Borsası.
Master of Science in Banking and Finance. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2021. Supervisor: Prof. Dr. Cahit Adaoğlu.
Keywords: Stock Exchange-Stock Exchange-Casablanca; The weak from efficiency; the random walk; the Casablanca Stock